Physical activity participant: engagement toward cognitive and physical function among rural veteran’s athletes / Siti Maizatul Akmal Mahbur and Wahidah Tumijan - Mahbur, Siti Maizatul Akmal; Tumijan, Wahidah (2024)
Engaging in physical activity is essential for preserving and enhancing cognitive and physical abilities, particularly for rural veteran athletes. Nevertheless, there is a dearth of research documenting the outcomes specifically for this age group. The study aimed to determine the relationship between physical activity, cognitive function, and physical function among rural veteran athletes. A cross-sectional correlational design was used. Data was collected using the Montreal Cognitive Assessment (MoCA), Sports Performance Physical Battery Test – Chair Stand Test (SPPB), Physical Activity Readiness Questionnaire for Everyone (PAR-Q+), and Community Health Activities Model Program for Seniors (CHAMPS). There is a significant moderately positive relationship (r = 0.460, p = 0.009) between physical activity for all activities and cognitive performance. Physical function showed a non-significant correlation (r = 0.346, p = 0.057) with physical activity for all activities. In conclusion, rural veteran athletes engage in a substantial amount of physical activity, meeting or exceeding recommended guidelines. There is a positive relationship between physical activity levels and cognitive function, indicating that higher physical activity is associated with better mental health. The relationship between physical activity and physical function is weak, suggesting that while physical activity.